PERBANDINGAN DOSIS PIRIDOSTIGMIN, PERFORMA FUNGSIONAL, DAN DERAJAT KLINIS PASIEN MIASTENIA GRAVIS SEBELUM DAN SETELAH TIMEKTOMI - Christianty Sugiarto; Sobaryati Sobaryati; Henny Anggraini Sadeli; Tri Wahyu Murni (NEURONA, 2018)
COMPARISON BETWEEN PYRIDOSTIGMINE DOSE, FUNCTIONAL PERFORMANCE, AND CLINICAL SEVERITY IN MYASTHENIA GRAVIS PATIENTS BEFORE AND AFTER THYMECTOMYABSTRACTIntroduction: Myasthenia gravis (MG) is highly associated with thymic abnormalities. Most cases, show decreasing dosage of drugs and improving of clinical symptoms after thymectomy. However, in Indonesia, there are only limited number of studies have evaluated it.Aim: To evaluate and compare clinical condition of MG patients in Hasan Sadikin Hospital, Bandung before and after thymectomy.Methods: A retrospective cohort and descriptive analytic study on adult MG patients who had gone through thymectomy in Hasan Sadikin Hospital, Bandung from January 2014 to December 2016. Daily Pyridostigmine dosage comparison, functional performance using Myasthenia Gravis-Activities of Daily Living (MG-ADL) score, and clinical severity using Myasthenia Gravis Foundation of America (MGFA) classification before and six months after thymectomy were assessed.Results: There are 27 subjects, female:male 2.8:1, with a mean age of 36.44±14.46 years. Average daily Pyridostigmine dosage needed pre- and six months post-thymectomy were 240 (180–540)mg and 180 (0–480)mg respectively. The median of MG-ADL scores pre- and six months post-thymectomy were 10 (4–21) and 3 (0–18) respectively. The median of MGFA classification pre-and six months post-thymectomy were grade IVa (IIa–V) and IIb (normal–V) respectively.Discussion: There were significant decrease in daily Pyridostigmine dosage, improvements in functional performance, and improvements in clinical severity six months after thymectomy in MG patients.Keywords: MG-ADL, MGFA classification, pyridostigmine, thymectomy ABSTRAKPendahuluan: Penyakit miastenia gravis (MG) sering berhubungan dengan kelainan kelenjar timus. Pada kebanyakan kasus, timektomi dapat menurunkan kebutuhan dosis obat dan memperbaiki gejala klinis pasien MG. Di Indonesia penelitian mengenai hal ini masih sangat terbatas.Tujuan: Mengetahui perbandingan kondisi klinis pasien MG antara sebelum dan setelah dilakukan timektomi di RSUP Dr. Hasan Sadikin, Bandung.Metode: Penelitian kohort retrospektif, deskriptif analitik pada pasien MG dewasa yang telah dilakukan timektomi di RSUP Dr. Hasan Sadikin, Bandung, antara Januari 2014-Desember 2016. Dilakukan perbandingan dosis Piridostigmin per hari serta penilaian performa fungsional dengan skor Myasthenia Gravis-Activities of Daily Living (MG-ADL) dan derajat klinis berdasarkan klasifikasi Myasthenia Gravis Foundation of America (MGFA) antara sebelum dan 6 bulan setelah timektomi.Hasil: Diperoleh 27 subjek, perempuan:laki-laki 2,8:1, rerata usia 36,4±14,5 tahun. Rerata dosis Piridostigmin per hari sebelum timektomi 240 (rentang 180-540)mg dan 6 bulan setelah timektomi 180 (0-480)mg. Median skor MG-ADL sebelum timektomi adalah 10 (4-21) dan 6 bulan setelah timektomi 3 (0-18). Median klasifikasi MGFA sebelum timektomi adalah IVa (rentang IIa-V) sedangkan 6 bulan setelah timektomi adalah IIb (rentang normal-V).Diskusi: Terdapat penurunan dosis Piridostigmin, serta perbaikan performa fungsional dan derajat klinis yang bermakna antara sebelum dan 6 bulan setelah timektomi pada pasien MG.Kata kunci: Klasifikasi MGFA, MG-ADL, piridostigmin, timektomi